Botando corpo (re)fazendo gêneros: uma pesquisa etnográfica sobre travestis e drag queens - Damásio, Anne Christine (2009)
I present a discussion on the making of the female body in the transvestites and drag queens, to understand how the body and the changes made are related to the construction of expressions of gender. Trying to articulate their thoughts on the relationship of gender and a range of appropriations / updates of the concept, informed by a focused ethnographic eye in the groups mentioned. Point bodies constructed as the place into which all my concerns, being ported as the main brand of the identity of the subject thus construct the text in question from these ethnographic short stories that have been developed on these subjects and their bodies, these subjects in their bodies.